Online Annex – Economic Challenges of Lagging Regions: Annex I – Country Case Studies - Adam Brown; Ben Gardiner; Roman Römisch; Jonathan Stenning (The Vienna Institute for International Economic Studies (wiiw), 2017)
This report is an annex to wiiw Research Report 421, 'Economic Challenges of Lagging Regions I Fiscal and Macroeconomic Environment'. It provides eight detailed country case studies, analysing the fiscal and macroeconomic environment in Bulgaria, Greece, Hungary, Italy, Poland, Portugal, Romania and Spain and its effects on the development of the lagging regions in those countries.
Keywords: E32; E60; H60; O11; O18; O40; R11; 330; macroeconomic development; regional economic development; EU; lagging regions; regional policy; economic challenges